Factors associated with infant feeding practices after hospital discharge Fatores associados à prática alimentar do recém-nascido pós-alta hospitalar - Celene Aparecida Ferrari Audi; A M S Corrêa; M R D O Latorre; Rafael Pérez-Escamilla (Universidade de São Paulo, 2005)
OBJECTIVE: To assess factors associated with infant feeding practices on the first day at home after hospital discharge. METHODS: A total of 209 women, who had a child aged four months or less and were living in Itapira, Brazil, were interviewed during the National Immunization Campaign Day in 1999. Statistical analysis was performed using the Chi-square test and a logistic regression model was used for verifying an association between dependent and independent variables. RESULTS: Women aged 25.5 years on average and 18.2% were teenagers. Fifty-three percent of the women delivered vaginally and most vaginal deliveries (78.5%) took place in the public hospital. The prevalence of exclusive breastfeeding on the first day at home was 78.1% and 11.6% of the infants were receiving formula at this time. The only factor associated with EBF on the first day at home was being a teenaged-primiparous mother (OR=9.40; 95% CI: 1.24-71.27). This association remained statistically significant even after controlling for type of delivery and hospital where the birth took place. Feeding formula on the first day at home was only significantly associated with the hospital (i.e., birth at the city hospital was a protective factor (OR=0.33; 95% CI: 0.13-0.86), even after controlling for vaginal delivery. CONCLUSIONS: On the first day at home after hospital discharge, teenaged-primiparous mothers were more likely to exclusive breastfeeding as well as those infants born in the municipal public hospital. Further studies are needed from a multidisciplinary approach. OBJETIVO: Avaliar os fatores associados à prática de amamentação no primeiro dia em casa após a alta hospitalar. MÉTODOS: Foram realizadas 209 entrevistas com mães de lactentes, com idade até quatro meses de vida, residentes em Itapira, SP, no momento em que levaram seus filhos para serem vacinados durante a Campanha Nacional de Vacinação, em 1999. Utilizou-se de análise exploratória dos dados, teste do qui-quadrado. Verificou-se associação entre as variáveis dependentes e independentes por análise de regressão logística. RESULTADOS: Observou-se, que a idade média das mães foi de 25,5 anos e 18,2% eram mães adolescentes. Nasceram por parto vaginal 53% dos lactentes, sendo a maioria (78,5%) em hospital municipal. Constatou-se que 78,1% dos lactentes no primeiro dia em casa encontravam-se em aleitamento materno exclusivo e 11,6% já haviam consumido outros alimentos. O único fator associado à maior chance de estar amamentando exclusivamente no primeiro dia em casa foi o fato de a mãe ser adolescente e primípara (OR=9,40; IC 95% (OR)=1,24-71,27), ajustado para o tipo de parto e hospital de nascimento. Em relação ao uso de leite artificial no primeiro dia em casa, a mãe atendida no hospital municipal teve menor chance de usar leite artificial (OR=0,33; IC 95% (OR)=0,13-0,86), mesmo após o controle para o parto vaginal. CONCLUSÕES: No primeiro dia em casa após alta hospitalar, adolescentes primíparas tiveram maior chance de amamentar exclusivamente, assim como aquelas crianças que nasceram no hospital municipal. Sugere-se a realização de outros estudos, que contemplem uma abordagem multidisciplinar.